2005
DOI: 10.1111/j.1751-1097.2005.tb00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects of Intrinsic and Extrinsic Aging of Human Skin: Beneficial Effects of Soy Extract

Abstract: Biochemical and structural changes of dermal connective tissue substantially contribute to the phenotype of aging skin. To study connective tissue metabolism with respect to ultraviolet (UV) exposure, we performed an in vitro (human dermal fibroblasts) and an in vivo complementary DNA array study in combination with protein analysis in young and old volunteers. Several genes of the collagen metabolism such as Collagen I, III and VI as well as heat shock protein 47 and matrix metalloproteinase‐1 are expressed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 33 publications
2
47
0
3
Order By: Relevance
“…In in vitro testing, genistein isoflavone is shown to stimulate collagen synthesis and downregulate matrix metalloproteinases (MMP) . Another study has reported that the use of soy extracts results in increased collagen synthesis in skin fibroblasts and the flattening of the dermal‐epidermal junction . Isoflavones have also been demonstrated to produce an anti‐aging effect on a UV‐damaged hairless mice model, which is partly due to its inhibitory effects on UV‐induced MMP‐1 expression and the subsequent collagen degradation .…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro testing, genistein isoflavone is shown to stimulate collagen synthesis and downregulate matrix metalloproteinases (MMP) . Another study has reported that the use of soy extracts results in increased collagen synthesis in skin fibroblasts and the flattening of the dermal‐epidermal junction . Isoflavones have also been demonstrated to produce an anti‐aging effect on a UV‐damaged hairless mice model, which is partly due to its inhibitory effects on UV‐induced MMP‐1 expression and the subsequent collagen degradation .…”
Section: Introductionmentioning
confidence: 99%
“…African-American skin is more compacted than Caucasian skin and which may add to more protection from maturing. Wrinkling in Asians is more and with less seriousness than in Caucasians [52,[26][27]55].…”
Section: Intrinsic Skin Ageing Factorsmentioning
confidence: 99%
“…Upotreba retinoida u dnevnoj nezi kože zahteva obavezno nanošenje proizvoda za zaštitu kože od sunca sa SPF 15 (najmanje) i što je moguće manje izlaganje direktnoj sunčevoj svetlosti. Estri retinola se bolje podnose nego retinol, dok retinaldehid ima sličan potencijal iritacije kao retinol (10,11).…”
Section: Kozmetički Retinoidiunclassified